2012
DOI: 10.1007/978-3-642-31869-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Fast Group Communication Scheduling in Duty-Cycled Multihop Wireless Sensor Networks

Abstract: Abstract. We study group communication scheduling in duty-cycled multi-hop wireless sensor networks. Assume that time is divided into time-slots and we group multiple consecutive time-slots into periods. Each node can transmit data at any time-slot while it only wakes up at its active time-slot of every period and thus be allowed to receive data. Under the protocol interference model, we investigate four group communication patterns, i.e., broadcast, data aggregation, data gathering, and gossiping. For each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The broadcast problem in duty-cycled scenarios has been studied in [19][20][21][22][23][24][25]. The MLB problem in duty-cycled scenarios is investigated in [19,20,24,25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The broadcast problem in duty-cycled scenarios has been studied in [19][20][21][22][23][24][25]. The MLB problem in duty-cycled scenarios is investigated in [19,20,24,25].…”
Section: Related Workmentioning
confidence: 99%
“…The MLB problem in duty-cycled scenarios is investigated in [19,20,24,25]. Hong et al [19] propose ELAC-SC algorithm, which achieves a ratio of ( 2 ), and the constant before 2 is 4| |.…”
Section: Related Workmentioning
confidence: 99%
“…To this end, only a handful of papers [21][22][23] have tried to address the MLBS problem in duty-cycled wireless networks, and even worse, all of these works only study the problem under the RTS/CTS model. Hong et al [21] prove that the MLBS problem in duty-cycled wireless networks is NP-hard and proposed two approximation algorithms with an approximation ratio of O(( 2 + 1)T) and 24T +1 respectively, where is the maximum degree.…”
Section: Related Workmentioning
confidence: 99%
“…Also, they showed that the total number of transmissions scheduled by OTAB is at most 15 times larger than the minimum number of transmissions. Recently, Xu et al [23] extended the pipelined broadcast scheme in [8] to consider duty-cycled WSNs. Their broadcast algorithm produces a latency of at most TR + TO(log 2 R), where the omitted constant in TO(log 2 R) also exceeds 150.…”
Section: Related Workmentioning
confidence: 99%
“…Duan et al [22] provide a generalized algorithm for the MLBSDC problem with an approximation ratio of T. They transform the MLBSDC problem into the conventional maximum independent set problem and try to find a maximum set of non-interfering senders in each time slot. Recently, Xu et al [23] extended the pipelined broadcast scheme in [16] to consider duty cycled WSNs. Their broadcast algorithm produces a latency of at most TH + TO(log 2 H), where the omitted constant in TO(log 2 H) also exceeds 150; in contrast, our solution has 108 as a constant in TO(log 2 H).…”
Section: Related Workmentioning
confidence: 99%